Synthesis and anticancer activity of some 2-[3/4-(2-substituted phenyl-2-oxoethoxy)benzylidene]-6-substituted-2,3-dihydro-1H-inden-1-one derivatives - Gündoğdu-Karaburun, Nalan; Karaburun, Ahmet Çağrı; Demirayak, Şeref; Kayagil, İsmail; Yurttaş, Leyla (Bentham Science Publishers, 2014)
The synthesis of 2-[3/ 4-(2-substituted phenyl-2-oxoethoxy) benzylidene]-6-substituted-2,3-dihydro-1H-inden-1one derivatives and the investigation of their anticancer activity were studied. 2-(3- or 4-Hydroxybenzylidene)-6substituted- 2,3-dihydro-1H-inden-1-ones were reacted with suitable 2-bromoacetophenones to give 2-[3/ 4-(2-substituted phenyl-2-oxoethoxy) benzylidene]-6-substituted-2,3-dihydro-1H-inden-1-one derivatives. The structure elucidation of the synthesised compounds was performed by IR, 1H-NMR, mass spectroscopic data and elemental analyses. The anticancer screening was carried out in National Cancer Institute (NCI), USA. Notable activity was obtained for some compounds.
WOS: 000335394500005
Keywords: 2,3-Dihydro-1H-Inden-1-One; Aurone Analogue; Anticancer Activity